Pemberdayaan UMKM melalui Pelatihan Digital Marketing untuk Peningkatan Daya Saing di Era Ekonomi Digital - Nur Aisyah Ramadhani (Journal of Community Action, 2025)
The rapid growth of digital technology has significantly influenced the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study aims to analyze the impact of digital marketing training on empowering MSMEs in Makassar to enhance competitiveness in the digital economy era. Using a qualitative descriptive method with participatory action research (PAR) design, data were collected through interviews, observations, and focus group discussions involving 25 MSME owners who participated in digital marketing training organized by local government and universities. The findings show that digital marketing training significantly improves MSME entrepreneurs’ digital literacy, marketing reach, and sales volume. The use of social media, e-commerce, and search engine optimization (SEO) techniques has enabled MSMEs to expand their markets and enhance brand visibility. The study concludes that continuous digital marketing training, supported by collaborative initiatives between academia, government, and private sectors, is essential to strengthen MSME competitiveness and sustainability in the digital economy era.